Native trees in Nug-as forest Key Biodiversity Area, Cebu, Philippines - Edgardo Lillo; ARCHIEBALD B. MALAKI; STEVE MICHAEL T. ALCAZAR; BERNARDO R. REDOBLADO; JOHN LOU B. DIAZ; JUANITA P. PINOTE; RAAMAH ROSALES; INOCENCIO E. BUOT JR (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Lillo EP, Malaki AB, Alcazar SMT, Redoblando BR, Diaz JLB, Pinote JP, Rosales R, Buot IE Jr. 2020. Native trees in Nug-as forest Key Biodiversity Area, Cebu, Philippines. Biodiversitas 21: 4162-4167. Threatened species, by definition, have a high probability of extinction, and so each of their populations significantly contributes to their survival. This paper presents a list of threatened Native trees in Nug-as forest of the Municipality of Alcoy, Cebu. A list of indicators was used to identify the conservation status of the Native trees at the local level. A total of 135 native trees from 48 families and 105 genera were recorded. Most species belong to the families of Euphorbiaceae, Lauraceae, Moraceae, Clusiaceae, Myrtaceae, Meliaceae, Fabaceae, and Rutaceae. In this study, 62 species were categorized as threatened, and 72 species as Least Concern, while in IUCN classification 19 threatened species were recorded, and 111 taxa considered as Least Concern respectively. Using the DENR method of classification 15 threatened species were recorded, and 115 taxa considered as Not Evaluated. The Nug-as forest was degraded by illegal cutting, kaingin, hunting and charcoal making. Based from Beynen and Townsend analysis, Nug-as forest was categorized as moderately disturbed. While DENR and IUCN declaration on the status of the Philippine native trees take a very long time, threatened plant species would be gone before we know it, considering the destruction rate in the Philippines.